(untitled) (Scientific journal of the Fergana State University, 2023)
It has been noted that the use of strains of the genus Botryococcus and Chlorococcum is appropriate for obtaining live feed with a complete nutritional content for the aquaculture industry, including a lower amount of protein (46.2-46.8%) and fat (26.2-26.4%). representatives of the genus Botryococcus were recorded as the genera of microalgae (Chlorococcum and Chlorella genera have high protein content (46.4-48.8%), but fat content (15.6-18.4%) is very low compared to all studied microalgae genera According to the results, representatives of the Botryococcus genus were recorded as microalgae genera that stored a relatively small amount of protein (46.2-46.8%) and fat (26.2-26.4%). Among them, representatives of the Chlorococcum and Chlorella genera stored protein. high (46.4-48.8%), however, oil storage (15.6-18.4%) was determined that it is very low compared to all studied microalgae genera.